2019
DOI: 10.4067/s0718-58392019000100017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amino acid biostimulant on the yield and nutraceutical potential of soybean

Abstract: Advancement in crop cultivation technologies strives to increase the yield and improve the quality of crops under minimized threats posed to the natural environment. Application of biostimulants is a treatment which increases crop yield and quality particularly after plants exposure to stress conditions. The objective of the work was to determine changes in yield and nutraceutical potential of soybean (Glycine max [L.] Merr.) 'Atlanta' after application of biostimulant. A field experiment was conducted in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 32 publications
5
28
0
Order By: Relevance
“…Their exogenous application allows the plant to save energy in their synthesis, thus increasing its capacity to use its resources for growth or to cope with stresses ( Popko et al, 2018 ). The positive effects of amino acid-based BSs are well known, and these products are widely marketed ( Botta, 2013 ; Cerdán et al, 2013 ; Popko et al, 2018 ; Kocira, 2019 ; Tadros et al, 2019 ). Most of the amino acids used are the 20 proteinogenic ones, but non-proteinogenic amino acids (npaa) can also be found.…”
Section: Amino Acids and Other N -Containing Compomentioning
confidence: 99%
“…Their exogenous application allows the plant to save energy in their synthesis, thus increasing its capacity to use its resources for growth or to cope with stresses ( Popko et al, 2018 ). The positive effects of amino acid-based BSs are well known, and these products are widely marketed ( Botta, 2013 ; Cerdán et al, 2013 ; Popko et al, 2018 ; Kocira, 2019 ; Tadros et al, 2019 ). Most of the amino acids used are the 20 proteinogenic ones, but non-proteinogenic amino acids (npaa) can also be found.…”
Section: Amino Acids and Other N -Containing Compomentioning
confidence: 99%
“…Biostimulants were used in terms when the foliar application of microelements is recommended. Their doses were established based on the authors' experience from previous investigations 35,38 .…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Although current predictions indicate a continuous increase in the use of biostimulants in both organic and sustainable agriculture, still little information can be found on the implementation of this agrotechnical treatment in bean cultivation. Our team has already conducted research on the influence of biostimulants on the yield and chemical composition of bean 14 , 19 , 35 37 and soybeans seeds 7 , 9 , 38 . The results clearly showed that the plant response depended on the composition and doses of the preparations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soya (Glycine max (L.) Merrill.) is one of the most important leguminous plants that are cultivated around the world because it is a precious source of both protein and fat [1,2]. Its use for production of food, oil, and fodder means that the demand for this plant is continuously growing [3].…”
Section: Introductionmentioning
confidence: 99%